A Comparison Analysis between the Traditional and Agile Project Management Approach - Aleidan, Abdulelah Fahad (2014)
Projects have grown in number and started to shape our society in the past decades, thus, it arises an important point which is the way they can be managed. Project management help organisations to achieve their goals through a developed structure. Construction projects have been using the traditional project management for a long time, yet the level of uncertainty in the construction environment today and the number of different sectors involved have changed. This has pointed to a gap between the used project management method in construction project and the way these projects are executed. In addition, the demand of applying new methods has been increasing and giving the for new project management approaches to be used.